Cost Management in Micro and Small Companies in the Mining Sector - Guidi, Antonio Carlos; Morgan, Levi; Montebelo, Maria Imaculada; Corrêa, Dalila Alves (Revista de Negócios, 2018)
According to Sebrae, micro and small companies represented 27% of the GDP in 2011 and 98.5% of all private companies in 2015. Despite this importance, in most cases they do not have employees with extensive cost management knowledge and the management practices of large companies are also repeated in them. Therefore, the aim of this paper is to analyze the operability of cost management at the micro and small companies that act in the mining and processing of dimension stones sector, searching for emphases on the presence of isomorphism. One hundred and sixty-two (162) companies were investigated in order to operationalize this study. Â A structured questionnaire was used as a data collection procedure. Three different approaches were used in the statistical analysis of the collected data: descriptive statistics; the Mann-Whitney U test and Fisherâ€™s exact test, and confirmatory and exploratory factor analysis. The results show the presence of mimetic isomorphism in the cost management practices of the companies researched. The research is limited to the sample, therefore, its findings can not be generalized. Based on this study, it was observed that future research should further develop the characterization of this economic phenomenon and study which resources would be required to improve management cost in micro and small companies in the analyzed segment. This is the first work that found the presence of mimetic isoformism among micro and small companies in the mining sector.